2004
DOI: 10.1074/jbc.m312806200
|View full text |Cite
|
Sign up to set email alerts
|

Conductance of Recombinant GABA Channels Is Increased in Cells Co-expressing GABAA A Receptor-associated Protein

Abstract: High conductance ␥-aminobutyric acid type A (GABA A ) channels (>40 picosiemens (pS)) have been reported in some studies on GABA A channels in situ but not in others, whereas recombinant GABA A channels do not appear to display conductances above 40 pS. Furthermore, the conductance of some native GABA A channels can be increased by diazepam or pentobarbital, which are effects not reported for expressed GABA A channels. GABARAP, a protein associated with native GABA A channels, has been reported to cause cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
71
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 16 publications
8
71
3
Order By: Relevance
“…At the macroscopic level, changes in the rates of receptor desensitization and deactivation have been reported in addition to an increase in the GABA EC 50 (concentration required to elicit a half-maximal response) (12). At the single channel level we have shown that increased single channel conductances (Ն40 pS) are associated with GABA A receptors co-expressed with GABARAP and that drugs are able to increase the conductance of these channels (9). The aim of the present study was to analyze the single channel properties of GABA A receptors co-expressed with GABARAP and to see if these newly acquired properties correlated with these receptors being organized at a higher density (i.e.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…At the macroscopic level, changes in the rates of receptor desensitization and deactivation have been reported in addition to an increase in the GABA EC 50 (concentration required to elicit a half-maximal response) (12). At the single channel level we have shown that increased single channel conductances (Ն40 pS) are associated with GABA A receptors co-expressed with GABARAP and that drugs are able to increase the conductance of these channels (9). The aim of the present study was to analyze the single channel properties of GABA A receptors co-expressed with GABARAP and to see if these newly acquired properties correlated with these receptors being organized at a higher density (i.e.…”
mentioning
confidence: 77%
“…We have, however, been able to mimic the behavior exhibited by neuronal extrasynaptic GABA A receptors in a recombinant system and change the dispersion of receptors in the membrane simply by co-expressing the trafficking protein GABARAP with GABA A receptors (9). GABARAP (GABA A receptor-associated protein) was originally identified because of its physical association with GABA A receptors following their isolation by immunoprecipitation from solubilized rat brain (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that functional modulation of GABA A Rs by binding of structurally altered GABARAP is responsible for the RP expression. When GABARAP is expressed with GABA A R composed of ␣1, ␤2/3, and ␥2 subunits in L929 fibroblasts, both single-channel conductance and mean open time of GABA A R are increased (Everitt et al, 2004;Luu et al, 2006). Considering that the majority of GABA A R subunits expressed in a PN are ␣1, ␤2/3, and ␥2, interaction of GABARAP and GABA A R␥2 might upregulate functional properties of GABA A R in a PN.…”
Section: Role Of Gabarap In Rpmentioning
confidence: 99%
“…Among them, we attended to GABARAP, a linker protein between GABA A R and tubulin (Wang et al, 1999). The number and/or function of surface GABA A R can be regulated by GABARAP in both heterologous expression systems and neurons (Chen et al, 2000(Chen et al, , 2005Nymann-Andersen et al, 2002;Everitt et al, 2004;Leil et al, 2004;Luu et al, 2006). However, implication of GABARAP in synaptic plasticity has not been explored.…”
Section: Introductionmentioning
confidence: 99%